The Effect of Spiritual Marketing on Consumer Loyalty - Ahmad Khairy; Mohamad Zaenal Abidin (Islamic Business and Management Journal, 2018)
The objective of this study is to describe the influence of spiritual product variables, the spiritual price, spiritual promotion against consumer loyalty (case study   Waroeng Spesial Sambal in Madiun). This type of the research design is associative causality. This research has two variables, namely the independent variable (X) is the Spiritual Product, Spiritual Price, Spiritual Promotion, and Spiritual Place, while the dependent variable (Y) is the loyalty of consumers “Waroeng Spesial Sambal in Madiun”. The population in this research is that consumers ever do the purchasing at Waroeng Spesial Sambal Madiun more than once. The sampling technique in this study using the technique of accidental sampling by the number of respondents determined as many as 75 respondents as samples. Analytical techniques used was multiple linear regression analysis technique. The data obtained through the respondents by using data form the collecting questionnaire/closed and measured using the Likert scale. The results showed that the spiritual products have no positive effect on consumer loyalty. Spiritual pricing does not positively affect consumer loyalty. Spiritual promotion has a positive effect on consumer loyalty. Spiritual places have a positive influence on consumer loyalty and the last two variables become the most dominant variable. The suggestions that can be submitted with regard to the results of this study are as follows (1) Waroeng Spesial Sambal Madiun should always improve or maintain the factors that have a positive effect on consumer loyalty such as rice added services as much, add branch facilities in the form of internal facilities or new branches. (2) Evaluate factors that do not positively affect the consumer loyalty that is varied sauce, and the suitability of price with product quality.